2021
DOI: 10.1177/1352458521999970
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing progressive MS rehabilitation research: A call from the International Progressive MS Alliance

Abstract: Background: People with multiple sclerosis (MS) experience myriad symptoms that negatively affect their quality of life. Despite significant progress in rehabilitation strategies for people living with relapsing-remitting MS (RRMS), the development of similar strategies for people with progressive MS has received little attention. Objective: To highlight key symptoms of importance to people with progressive MS and stimulate the design and implementation of high-quality studies focused on symptom management and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 93 publications
0
8
0
2
Order By: Relevance
“…As exercise training is becoming a vital component in the therapeutic toolbox of MS patients, to date, international guidelines are available [ 18 ]. Rehabilitation groups, e.g., International Progressive MS Alliance, have suggested that future research should focus on progressive MS rehabilitation and investigate the effect of exercise on the pattern of disease progression in these patients [ 19 ]. It is worth mentioning that pioneers in the field developed a framework to strengthen the standardization, quality and scope of MS rehabilitation studies that would help PwMS with their quality of life (MoXFo initiative) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As exercise training is becoming a vital component in the therapeutic toolbox of MS patients, to date, international guidelines are available [ 18 ]. Rehabilitation groups, e.g., International Progressive MS Alliance, have suggested that future research should focus on progressive MS rehabilitation and investigate the effect of exercise on the pattern of disease progression in these patients [ 19 ]. It is worth mentioning that pioneers in the field developed a framework to strengthen the standardization, quality and scope of MS rehabilitation studies that would help PwMS with their quality of life (MoXFo initiative) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the existence of barriers to research following COVID-19 echoes findings from other fields, 1 , 9 including reports of widespread closure of facilities and limitations accessing funding, we have shown how a number of unique challenges exist for MS rehabilitation/QoL research specifically, including many that existed prior to the pandemic and which therefore may be expected to continue should face-to-face research recommence. Given the call to prioritize areas of research supporting people with progressive MS in particular, 10 it is vital that any barriers to research in the area of rehabilitation and QoL are tackled. It is also important that such obstacles are taken into account when planning how best to support researchers over the coming years, which will in turn have implications for the successful symptom management and wellbeing of PwMS.…”
Section: Discussionmentioning
confidence: 99%
“…While all centres have been scrupulous in following government, provincial, local health authority and institutional mandates for continuing research, we needed to take into account the potential benefits of the interventions (which are unknown, hence the study) versus the risks to participants and staff of coming into medical institutions that in the majority of sites are also hospitals where COVID-19 patients were being treated. In weighing these competing factors, the investigators were aware that an important driving force behind CogEx is the dearth of rigorous, large scale empirical, multicentre rehabilitation data in people with progressive MS [12][13][14]. Furthermore, the study has been embraced by many of the participants who, historically as a group, have felt overlooked by MS researchers whose attention has focused predominantly on people with relapsing-remitting forms of the disease.…”
Section: Discussionmentioning
confidence: 99%